2022
DOI: 10.1186/s43014-022-00083-3
|View full text |Cite
|
Sign up to set email alerts
|

Production and evaluation of novel functional extruded corn snacks fortified with ginger, bay leaves and turmeric powder

Abstract: Extruded corn snacks are accepted by all human ages especially children, but they have low functional value. Therefore, corn extruded snacks contain rich nutraceuticals dried herbs including Laurus nobilis (T1), Curcuma longa (T2), Zingiber officinale Roscoe (T3), and the mixture of these herbs (T4) were manufactured and analyzed. The results declared that all the herbal extruded corn snacks had significantly higher ash, fibers, minerals, and vitamins A and B6. For minerals, the highest percent of increase com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 78 publications
3
14
0
Order By: Relevance
“…Color changes are affected by thermal processes that may produce Maillard reactions, caramelization, hydrolysis, and pigment degradation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Color changes are affected by thermal processes that may produce Maillard reactions, caramelization, hydrolysis, and pigment degradation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing a base material with fruits, vegetables, herbs, seeds or by-products of the agri-food industry increases the nutritional value of the extruded food end-product by providing antioxidants, polyphenols, vitamins and minerals [12]. Moreover, the choice of process conditions allows preservation of their nutritional value and may increase the bioavailability of some bioactive ingredients as confirmed by the studies of Amer and Rizk [13], whose work showed an increase in the content of phenolic compounds in food end-products extruded from base material and plant additives.…”
Section: Introductionmentioning
confidence: 91%
“…Other new products that can be made from ginger are skin/stick, osmotically dried appetizing ginger flakes, ginger drinks, and ginger starch [88]. Amer et al [89] developed value-added extruded maize enriched with ginger extract at 3%. The product had better functional and sensory properties.…”
Section: Gingermentioning
confidence: 99%